RESPONSE OF ECO ENZYME AND RHIZOBIUM ISOLATION ON GROWTH AND PRODUCTION RED ONION (Allium ascolonicum L) - Yudi Siswanto; Isnar Sumartono; Mujaddin Ilman (International Forum of Researchers and Lecturers, 2023)
Response of Eco Enzyme Administration and Rhizobium Isolation on the Growth and Production of Shallots (Allium ascolonicum L). This study aims to determine the effectiveness of eco enzyme administration and rhizobium isolation as well as the interaction of eco enzyme and rhizobium isolation on the growth and production of shallots (Allium ascolonicum L). This study used a factorial randomized block design (RBD) consisting of 2 factors, 16 treatments, and 3 blocks. The results showed that the effectiveness of eco enzyme administration and rhizobium isolation had an effect on the parameters of plant height (cm), number of leaves (strands), number of tubers per sample (tubers), wet tuber production per sample (g), wet tuber production per plot ( g), dry tuber production per sample (g), dry tuber production per plot (g). The interaction between the effectiveness of eco enzyme administration and rhizobium isolation had no effect on plant height (cm), number of leaves (strands), number of tubers per sample (tubers), wet tuber production per sample (g), wet tuber production per plot (g), dry tuber production per sample (g), dry tuber production per plot (g).